Caracterização de habitats em áreas de proteção marinha através de imageamento com veículo de operação remota (ROV) - Silva, Diego Bezerra de Melo e (2019)
Studies of characterization of benthic communities and habitats are of paramount importance in the elaboration of management plans and in the preservation of marine biodiversity, especially in areas of marine protection, regions considered of relevant ecological interest. At the Santa Cruz Wildlife Refuge (RVS) and the Environmental Protection Area (APA) in the state of Espirito Santo, there are several potentially anthropogenic activities that cause impacts, such as fishing activity and exploration and production of oil and gas occurring near the region. The objective of this study was to characterize the main habitats in the region of the RVS of Santa Cruz and the APA Costa das Algas, using remotely operated vehicle (ROV) imaging techniques and its correlation with the sedimentological material. The records were obtained through 50 collection stations distributed along the continental shelf, from the 10 m isobath. Five habitats were identified and described as Terrestrial Sands, Carboniferous Gravels, Rodoliths and Gravels, Reefs and Rodolites and Laterites (Hardground), refining the level of knowledge in relation to that already existing in past and more regional studies of the study area. It was possible to identify a greater abundance in the habitat described as Reefs and Rodolites, located in the deeper portion of the APA Costa das Algas, having as opposite the Terrestrial Sands habitat, mostly comprising at the RVS of Santa Cruz. The method used proved to be satisfactory for this type of characterization, which can be replicated in studies of more sensitive areas. The results obtained in the present study will be able to subsidize the managing organ of the two protected areas in the elaboration of their respective management plans.